NADPH oxidase inhibitor regulates microRNAs with improved outcome after mechanical reperfusion - Liu, Zhong; Tuo, Yong-Hua; Chen, Jian-Wen; Wang, Qing-Yuan; Li, Songlin; Li, Ming-Chang; Dai, Gang; Wang, Jin-Shan; Zhang, Yong-Li; Feng, Lei; Shi, Zhong-Song (Journal of neurointerventional surgery, 2017)
BackgroundInhibition of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) pathway improves the neurological outcome in the transient middle cerebral artery occlusion (tMCAO) animal model. In this study we analyzed the microRNAs profile targeting NOX2 and NOX4 genes and its response to NOX2/4 inhibitor VAS2870 to understand the mechanisms of this protective effect.MethodsThe intraluminal filament tMCAO model was established in hyperglycemic rats (n=106) with 5 hours ischemia followed by 19 hours reperfusion. NOX inhibitor VAS2870 was delivered intravenously before reperfusion. Infarct volume, hemorrhagic transformation, and mortality were determined at 24 hours after cerebral ischemia. MicroRNAs profile targeting NOX2 and NOX4 genes were predicted by microRNA databases and further evaluated by microRNA microarray and quantitative RT-PCR.ResultsTen microRNAs potentially targeting NOX2 and NOX4 genes (including microRNA-29a, microRNA-29c, microRNA-126a, microRNA-132, microRNA-136, microRNA-138, microRNA-139, microRNA-153, microRNA-337, and microRNA-376a) were significantly downregulated in the ischemic hemisphere in the tMCAO group compared with the sham-operated group, as shown by microRNA microarray and quantitative RT-PCR (all p<0.05). Intravenous treatment with NOX inhibitor VAS2870 before reperfusion increased the expression of microRNA-29a, microRNA-29c, microRNA-126a, and microRNA-132 compared with the tMCAO group (all p<0.05).ConclusionsSeveral microRNAs potentially targeting NOX2 and NOX4 genes displayed altered levels in hyperglycemic rats with the tMCAO model, suggesting their regulatory roles and targeting potentials for acute ischemic stroke treatment. Targeting specific microRNAs may represent a novel intervention opportunity to improve outcome and reduce hemorrhagic transformation after mechanical reperfusion for acute ischemic stroke.